Toward Democracy and Democratisation: The Impact of the Donald Trump Administration on the Latest Authoritarian Actions of Vladimir Putin and Jinping Xi - OCHE, JAMESLEO (İstanbul Kültür Üniversitesi, 2022)
The key questions underpinning the current academic debate on the Trump administration are: How do we conceptualize the Trump 'America First' foreign policy? What are the actual executive orders, policies and actions of the Trump administration? How do these executive orders, policies and actions shift from U.S traditional foreign policy of democracy promotion to the authoritarian objectives of Putin and Xi? This study aims to find answers to these questions, why arguing that: 1) the Trump foreign policy centered on an isolationist grand strategy to U.S role in global politics; 2) the Trump administration is a huge gain for authoritarians like Putin and Xi, and a hug loss for democracy; 3) a decline of democracy in the U.S is likely to lead to global decline if a certain U.S administration does not prioritize democracy promotion.
Demokrasiye Ve Demokratikleşmeye Doğru: Donald Trump Yönetiminin Vladimir Putin Ve Jinping Xi'nin Son Otoriter Eylemleri Üzerindeki Etkisi
▪ Yüksek lisans tezi.
Keywords: Democracy Promotion; America First Foreign Policy